Pengaruh Bahan dan Ukuran Kemasan Produk Biji Kopi terhadap Minat Beli Pelanggan di Pippo Coffee Roasters, Batam - Tegar Fatihah; Dailami .; Wahyudi Ilham; Tito Pratama (CV. ITTC INDONESIA, 2025)
Coffee consumption trends in Indonesia continue to rise in line with the growth of the local coffee industry and increasing public interest in packaged coffee bean products. In this highly competitive market, packaging plays a crucial role—not only as protection for the product but also as part of a marketing strategy that can influence consumers’ purchase intention. This study aims to analyze the effect of packaging material and packaging size on customers’ purchase intention at Pippo Coffee Roasters. The research employs a descriptive quantitative approach with 121 respondents determined using the Slovin formula from a population of 2,350 people over a three-month period, with a margin of error of 0.09. Data were analyzed using SPSS version 30 through a series of statistical tests, including validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), as well as multiple linear regression analysis consisting of t-tests, F-tests, and the coefficient of determination. The results indicate that the research instruments covering the variables of packaging material, packaging size, and purchase intention were valid, reliable, and met the classical assumption tests. Regression analysis shows that the packaging material of coffee bean products has a significant effect on customers’ purchase intention, while packaging size does not have a significant partial effect. However, simultaneously, both variables have a significant effect on purchase intention, with a coefficient of determination (R²) value of 71.6%. These findings can serve as practical guidance for business owners, especially in the coffee industry, in designing packaging that not only maintains product quality but also enhances customers’ purchase intention.